Proof of the Markov Property when Taking “Two steps at a time”.
I have seen the solution, but I would like to understand how it actually works.
A new variable is defined, $Z_n = (X_n, X_{n-1})$, this is kind of like the join probability of 2 consecutive steps; the smallest value of n in this case is 1. The proof proceeds as follows:
$P(Z_n = z_n|Z_{n-1}, Z_{n-2}...Z_1 = z_1)$
The above is equal to : $P(X_n = x_n, X_{n-1} = x_{n-1}|X_{n-1} = x_{n-1}, X_{n-2} = x_{n-2}...X_1 = x_1)$
Which is equal to: $P(X_n = x_n|X_{n-1} = x_{n-1})$
Which finally, is equal to : $P(Z_n=z_n|Z_{n-1} = z_{n-1})$
I'm struggling to understand how the RHS of the 2nd step came about, and also why the 3rd step automatically implies the last step is true.
Your help would be appreciated greatly, thanks in advance !
stochastic-processes markov-chains random-walk
add a comment |
I have seen the solution, but I would like to understand how it actually works.
A new variable is defined, $Z_n = (X_n, X_{n-1})$, this is kind of like the join probability of 2 consecutive steps; the smallest value of n in this case is 1. The proof proceeds as follows:
$P(Z_n = z_n|Z_{n-1}, Z_{n-2}...Z_1 = z_1)$
The above is equal to : $P(X_n = x_n, X_{n-1} = x_{n-1}|X_{n-1} = x_{n-1}, X_{n-2} = x_{n-2}...X_1 = x_1)$
Which is equal to: $P(X_n = x_n|X_{n-1} = x_{n-1})$
Which finally, is equal to : $P(Z_n=z_n|Z_{n-1} = z_{n-1})$
I'm struggling to understand how the RHS of the 2nd step came about, and also why the 3rd step automatically implies the last step is true.
Your help would be appreciated greatly, thanks in advance !
stochastic-processes markov-chains random-walk
add a comment |
I have seen the solution, but I would like to understand how it actually works.
A new variable is defined, $Z_n = (X_n, X_{n-1})$, this is kind of like the join probability of 2 consecutive steps; the smallest value of n in this case is 1. The proof proceeds as follows:
$P(Z_n = z_n|Z_{n-1}, Z_{n-2}...Z_1 = z_1)$
The above is equal to : $P(X_n = x_n, X_{n-1} = x_{n-1}|X_{n-1} = x_{n-1}, X_{n-2} = x_{n-2}...X_1 = x_1)$
Which is equal to: $P(X_n = x_n|X_{n-1} = x_{n-1})$
Which finally, is equal to : $P(Z_n=z_n|Z_{n-1} = z_{n-1})$
I'm struggling to understand how the RHS of the 2nd step came about, and also why the 3rd step automatically implies the last step is true.
Your help would be appreciated greatly, thanks in advance !
stochastic-processes markov-chains random-walk
I have seen the solution, but I would like to understand how it actually works.
A new variable is defined, $Z_n = (X_n, X_{n-1})$, this is kind of like the join probability of 2 consecutive steps; the smallest value of n in this case is 1. The proof proceeds as follows:
$P(Z_n = z_n|Z_{n-1}, Z_{n-2}...Z_1 = z_1)$
The above is equal to : $P(X_n = x_n, X_{n-1} = x_{n-1}|X_{n-1} = x_{n-1}, X_{n-2} = x_{n-2}...X_1 = x_1)$
Which is equal to: $P(X_n = x_n|X_{n-1} = x_{n-1})$
Which finally, is equal to : $P(Z_n=z_n|Z_{n-1} = z_{n-1})$
I'm struggling to understand how the RHS of the 2nd step came about, and also why the 3rd step automatically implies the last step is true.
Your help would be appreciated greatly, thanks in advance !
stochastic-processes markov-chains random-walk
stochastic-processes markov-chains random-walk
asked Nov 20 '18 at 22:25
PEze
61
61
add a comment |
add a comment |
1 Answer
1
active
oldest
votes
You can use the rule $P(AB|C) = P(A|BC)P(B|C)$ on step 2, where $A$ is the event $X_n=x_n$, $B$ is the event $X_{n-1}=x_{n-1}$, and $C$ is the event $X_{n-1}=x_{n-1}, ; ... ; X_1=x_1$. By the Markov property, you can see that $P(A|BC)$ will simply reduce to $P(A|B)$. Given the definition of $B$ and $C$, it is trivial to see why $P(B|C) = 1$. This will lead you from step 2 to step 3.
Let's expand step 4:
$P(Z_n=z_n|Z_{n-1}=z_{n-1})$
$=P(X_n=x_n, X_{n-1}=x_{n-1}|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$
$=P(X_n=x_n|X_{n-1}=x_{n-1}, X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (using $P(AB|C) = P(A|BC)P(B|C)$)
$=P(X_n=x_n|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (removing redundant term)
$=P(X_n=x_n|X_{n-1}=x_{n-1})$ (Markov property)
add a comment |
Your Answer
StackExchange.ifUsing("editor", function () {
return StackExchange.using("mathjaxEditing", function () {
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
});
});
}, "mathjax-editing");
StackExchange.ready(function() {
var channelOptions = {
tags: "".split(" "),
id: "69"
};
initTagRenderer("".split(" "), "".split(" "), channelOptions);
StackExchange.using("externalEditor", function() {
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled) {
StackExchange.using("snippets", function() {
createEditor();
});
}
else {
createEditor();
}
});
function createEditor() {
StackExchange.prepareEditor({
heartbeatType: 'answer',
autoActivateHeartbeat: false,
convertImagesToLinks: true,
noModals: true,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
imageUploader: {
brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
allowUrls: true
},
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
});
}
});
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3006985%2fproof-of-the-markov-property-when-taking-two-steps-at-a-time%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
1 Answer
1
active
oldest
votes
1 Answer
1
active
oldest
votes
active
oldest
votes
active
oldest
votes
You can use the rule $P(AB|C) = P(A|BC)P(B|C)$ on step 2, where $A$ is the event $X_n=x_n$, $B$ is the event $X_{n-1}=x_{n-1}$, and $C$ is the event $X_{n-1}=x_{n-1}, ; ... ; X_1=x_1$. By the Markov property, you can see that $P(A|BC)$ will simply reduce to $P(A|B)$. Given the definition of $B$ and $C$, it is trivial to see why $P(B|C) = 1$. This will lead you from step 2 to step 3.
Let's expand step 4:
$P(Z_n=z_n|Z_{n-1}=z_{n-1})$
$=P(X_n=x_n, X_{n-1}=x_{n-1}|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$
$=P(X_n=x_n|X_{n-1}=x_{n-1}, X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (using $P(AB|C) = P(A|BC)P(B|C)$)
$=P(X_n=x_n|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (removing redundant term)
$=P(X_n=x_n|X_{n-1}=x_{n-1})$ (Markov property)
add a comment |
You can use the rule $P(AB|C) = P(A|BC)P(B|C)$ on step 2, where $A$ is the event $X_n=x_n$, $B$ is the event $X_{n-1}=x_{n-1}$, and $C$ is the event $X_{n-1}=x_{n-1}, ; ... ; X_1=x_1$. By the Markov property, you can see that $P(A|BC)$ will simply reduce to $P(A|B)$. Given the definition of $B$ and $C$, it is trivial to see why $P(B|C) = 1$. This will lead you from step 2 to step 3.
Let's expand step 4:
$P(Z_n=z_n|Z_{n-1}=z_{n-1})$
$=P(X_n=x_n, X_{n-1}=x_{n-1}|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$
$=P(X_n=x_n|X_{n-1}=x_{n-1}, X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (using $P(AB|C) = P(A|BC)P(B|C)$)
$=P(X_n=x_n|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (removing redundant term)
$=P(X_n=x_n|X_{n-1}=x_{n-1})$ (Markov property)
add a comment |
You can use the rule $P(AB|C) = P(A|BC)P(B|C)$ on step 2, where $A$ is the event $X_n=x_n$, $B$ is the event $X_{n-1}=x_{n-1}$, and $C$ is the event $X_{n-1}=x_{n-1}, ; ... ; X_1=x_1$. By the Markov property, you can see that $P(A|BC)$ will simply reduce to $P(A|B)$. Given the definition of $B$ and $C$, it is trivial to see why $P(B|C) = 1$. This will lead you from step 2 to step 3.
Let's expand step 4:
$P(Z_n=z_n|Z_{n-1}=z_{n-1})$
$=P(X_n=x_n, X_{n-1}=x_{n-1}|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$
$=P(X_n=x_n|X_{n-1}=x_{n-1}, X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (using $P(AB|C) = P(A|BC)P(B|C)$)
$=P(X_n=x_n|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (removing redundant term)
$=P(X_n=x_n|X_{n-1}=x_{n-1})$ (Markov property)
You can use the rule $P(AB|C) = P(A|BC)P(B|C)$ on step 2, where $A$ is the event $X_n=x_n$, $B$ is the event $X_{n-1}=x_{n-1}$, and $C$ is the event $X_{n-1}=x_{n-1}, ; ... ; X_1=x_1$. By the Markov property, you can see that $P(A|BC)$ will simply reduce to $P(A|B)$. Given the definition of $B$ and $C$, it is trivial to see why $P(B|C) = 1$. This will lead you from step 2 to step 3.
Let's expand step 4:
$P(Z_n=z_n|Z_{n-1}=z_{n-1})$
$=P(X_n=x_n, X_{n-1}=x_{n-1}|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$
$=P(X_n=x_n|X_{n-1}=x_{n-1}, X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (using $P(AB|C) = P(A|BC)P(B|C)$)
$=P(X_n=x_n|X_{n-1}=x_{n-1},X_{n-2}=x_{n-2})$ (removing redundant term)
$=P(X_n=x_n|X_{n-1}=x_{n-1})$ (Markov property)
answered Dec 3 '18 at 3:00
Aditya Dua
83918
83918
add a comment |
add a comment |
Thanks for contributing an answer to Mathematics Stack Exchange!
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
Use MathJax to format equations. MathJax reference.
To learn more, see our tips on writing great answers.
Some of your past answers have not been well-received, and you're in danger of being blocked from answering.
Please pay close attention to the following guidance:
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
To learn more, see our tips on writing great answers.
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3006985%2fproof-of-the-markov-property-when-taking-two-steps-at-a-time%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown